1980
DOI: 10.1111/j.1365-3059.1980.tb01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical control of onion fly, Delia antiqua (Meig.)

Abstract: SUMMARY In eight field plot trials in Cambridgeshire and Bedfordshire in 1977–79, insecticidal seed treatments and granules were tested against onion fly larvae. Carbophenothion, chlorfenvinphos, dieldrin, fonofos, iodo‐fenphos, permethrin and pirimiphos‐ethyl were tested as seed treatments in soil. Chlorpyrifos, dieldrin and pirimiphos‐ethyl were tested as seed treatments in peat blocks. Chlorfenvinphos and pirimiphosethyl were also tested as granules incorporated in soil and in peat blocks. Pirimiphos‐ethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Despite this high level of pest control, chlorpyrifos‐treated seedlings did not appear as healthy as those that had grown from tefluthrin‐treated seed. It is possible that this was because of phytotoxicity as chlorpyrifos has been shown to affect the growth of onions (Emmett & Savage, 1980) and brassicas (Straub 1988; Steene, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this high level of pest control, chlorpyrifos‐treated seedlings did not appear as healthy as those that had grown from tefluthrin‐treated seed. It is possible that this was because of phytotoxicity as chlorpyrifos has been shown to affect the growth of onions (Emmett & Savage, 1980) and brassicas (Straub 1988; Steene, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The analytical review of scientific literature showed the lack of research to study the biological features of development and harmfulness of the entomocomplex of onions with modern cultivation technologies and depending on the phase of development of the crop. [16,17]. After all, the damage to onions during the growing season by some pests leads both to reduced yields, infection with a complex of infectious diseases, and the death of young plants [18,19].…”
Section: Introductionmentioning
confidence: 99%